Microbenthic Net Metabolism Along Intertidal Gradients (Cadiz Bay, SW Spain): Spatio-Temporal Patterns and Environmental Factors - Haro, Sara; Lara, Miguel; Laiz, Irene; González, Carlos José; Bohórquez, Julio; Garcia-Robledo, Emilio; Corzo, Alfonso; Papaspyrou, Sokratis (Frontiers in Marine Science, 2020)
The changes in the annual biomass distribution of microphytobenthos (MPB) have been addressed by different studies, although this information is scarce in southern European coastal systems when compared to Northern European estuaries. Moreover, there is little information regarding annual changes in the primary production of MPB related with those in the annual biomass. For this reason, we followed the net production in light, dark respiration rates (determined by oxygen microelectrodes) and MPB abundance (estimated by sediment chlorophyll a) along an intertidal gradient of the inner Cadiz Bay during an annual cycle. Sediment cores were collected seasonally along two transects (5 sampling stations per transect) with contrasting sediment granulometry: muddy (Puerto Real, PR) and muddy-sandy (San Fernando, SF). Our results show that MPB biomass and net production increased seawards reaching maxima in winter. The seasonal maximum of daily solar irradiance and high temperature reached in summer in southern Spain likely inhibits MPB production. Spatial patterns of MPB biomass and net production depend on season and environmental heterogeneity. Environmental variables, analyzed by principal component analyses, were used to explain the variability of MPB metabolism by multiple regression. The principal component axes explained up to 60 % of the microphytobenthic net production and 41 % of the respiration rates in the PR transect while they only explained about 25 % of the same rates in SF. The variability in the environmental variables contributing to the observed patterns implies that no single set of variables can be used to predict net production patterns in the entire system. The different patterns of net production observed between transects highlight the importance of considering the spatial heterogeneity of our system to estimate the contribution of MPB to the inner Cadiz Bay productivity. This production is of major importance since our data showed that microphytobenthic production can contribute up to 49 % of the total benthic production of intertidal sediments of the inner Cadiz Bay.